Will a legacy of enhanced resource availability accelerate the soil microbial response to future climate change?. (February 2022) - Yuan, Mingyue; Na, Meng; Hicks, Lettice C.; Rousk, Johannes
Abstract: Soil microorganisms play an integral role in the regulation of carbon (C) cycling. In high-latitude ecosystems, climate warming is leading to higher plant productivity, shrub expansion and faster nutrient cycling; all of which increase resource availability to soil microorganisms. To understand how a legacy of enhanced resource availability affects the functional traits of microbial communities, and their feedbacks to further environment change, we collected soils from a field-experiment in a subarctic dry heath, where the consequences of climate warming were simulated by adding birch litter or inorganic N as either chronic additions during three years or as a single extreme addition. Soils were then re-exposed to the same resource or a modified resource environment in the laboratory and were monitored for 2 months. We hypothesized that a history of resource input would affect microbial functional profiles, which could result in two possibilities: 1) soil microbes exposed to a historical resource input would perform better when presented with the same resource, because the communities would be specialized to use the added resource, or 2) soil microbes would perform better when presented with a new resource, because the added resource would relieve the nutrient limitation induced by the previous resource input. We also hypothesized that with the same resource, a chronic and long-term input (i.e., a press disturbance) would select for K-strategists (i.e., fungi), while a sudden and large input (i.e., a pulse disturbance) would select for r-strategists (i.e., bacteria). We observed that bacteria in soils exposed to a history of N input showed a stronger growth response to new litter addition, while fungi in soils with a history of litter input showed a stronger growth response to both new litter and new N additions. When presented with new litter, the increase of fungal growth in soil from the extreme litter field-treatment was lower than in the chronic litter field-treatment, demonstrating that a pulse disturbance could weaken the stimulation of fungal growth. When presented with new litter, the increases of bacterial growth did not differ between the chronic N field-treatment and the extreme N field-treatment, suggesting that bacterial responses were not favoured by a press disturbance. We conclude that the enhanced resource availabilities expected in warming arctic soils will generate a positive microbial feedback to climate change. Highlights: A legacy of enhanced resource availability modulated microbial resource-responses. A legacy of N input strengthened the bacterial growth-response to new litter. A legacy of litter input strengthened the fungal growth-response to both new litter and N. Fungal resource-responses were strengthened more by longer-term, stable change.